ANALYSIS OF USER EXPERIENCE OF DANA E-WALLET USING USER EXPERIENCE QUOSTIONNAIRE (UEQ) AND UX HONEYCOMB - Nyimas Silvia; Allsela Meiriza; Nabila Rizky Oktadini; Pacu Putra (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2024)
In the era Society 5.0, economic growth and digital products have mushroomed, leading to digital transaction product innovation becoming a daily necessity for society. Easy, cashless payment are made through an E-wallet application with various options, including the DANA application. However, in several reviews, user have complained about the performance and issues with the DANA application such as, the display is unclear when logging into the application, and it loads slowly when entering the amount of money. This research was conducted to evaluate DANA application users and provide recommendation for improvements and enhancements to enhance the DANA application user experience. From the result of the value proposition on the implementation of the UX Honeycomb method in the DANA application between the people of Palembang City, users generally agree that DANA deserves a good above-average rating. Meanwhile, the User Experience Questionnaire (UEQ) method show that the DANA application received positive scores on the attractive, perspicuity, dependability, efficiency, and stimulation variables, but it obtained a negative score on the novelty variable. Thus, the DANA application need to design and create more creative, intentional, and innovative products.